Indigenous Lactic Acid Bacteria as Antioxidant Agents in the Production of Organic Raw Fermented Sausages - Anna Łepecka; Piotr Szymański; Anna Okoń (MDPI AG, 2024)
The study aimed to assess the impact of lactic acid bacteria (LAB) strains on the antioxidant, physico-chemical properties, and microbiological quality of fermented sausages. Five treatments of raw sausages were prepared: two controls without LAB addition (C, P), and three samples with LAB addition (SCH1, BAL6, KL14). Fatty acid composition, cholesterol content, physico-chemical, microbiological tests, and antioxidant assays, were performed at time 0 and after 1 and 2 months of storage. A significantly higher ability to scavenge free radicals of DPPH (2,2-diphenyl-1-picrylhydrazyl) was found in sausages with all LAB strains. In the case of the ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) test, it was noted that KL14 treatment had higher antioxidant activity. The main fatty acids in sausages were monounsaturated and saturated. A significantly lower cholesterol content was observed in sausages with the addition of LAB. Sausages with LAB strains differed significantly in pH value. Water activity decreased significantly during storage. After 2 months of storage, the sausages with BAL6 and KL14 strains were characterized by significantly lower redox potential and a lower TBARS (thiobarbituric acid reactive substances) index. It was found that P sausages had the darkest color. SCH1, BAL6, and KL14 strains were also capable of producing red color. The total number of microorganisms in the sausages was high, which is mainly due to the high LAB content and yeast and mold counts. No spoilage or pathogenic microflora were detected. Indigenous LAB strains have the potential to improve the quality and safety of fermented meat products.